Pengaruh Return On Asset, Asset Growth, Sales Growth Terhadap Dividend Payout Ratio Pada Perusahaan Manufaktur Yang TercatatDi Bursa Efek Indonesia - Elistya Rimawati (Jurnal Ilmiah SINUS, 2012)
The main reason poeple invert is to make a profit. It is reasonable if investors demand a certain level of return on funds that has been invested. Investor expectations of investment returns is that conpensation of  opportunity costs and risk reduduction in purchasing power due to the effects of inflation. How big the company in determines the dividend policy can be seen from Devidend Payout Ratio.          The basic formulation of the problem is as follows: Is there any influence of Return on Asset of Dividend Payout Ratio (DPR)? Is there an effect of Sales growth of Dividend Payout Ratio (DPR)? That there any effects of Asset growth of Dividend Payout Ratio (DPR)? Results of regression analysis showed that large numbers of regression coefisien of Return on Assets (2.098) Assets Growth (-o.980) and Sales Growth (-0.225). Based on the regression coefficients of  the 3rd. It’s concluded that the hypothesis: Return On Asset positive influence on Divident Payout Ratio is significantly tested. Asset growth negative influence on Dividend Payout Ratio is not tested and not signifient. That Sales Growth Significantly are positively influence the Dividend Payout Ratio is not tested and not significant.Key : return on asset, asset growth, sales growth, divident payout ratio